2010
DOI: 10.2169/internalmedicine.49.3227
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine Treatment in a Patient Suffering from Progressive Multifocal Leukoencephalopathy after Umbilical Cord Blood Transplant

Abstract: We report herein the case of a 37-year-old man who developed probable progressive multifocal leukoencephalopathy (PML) following an umbilical cord blood transplant. The patient showed favorable clinical, neuroradiological and virological responses after treatment with mefloquine, an anti-malarial drug. Mefloquine may offer some benefits as a treatment for PML in patients with or without human immunodeficiency virus type-1 infection. This report highlights the need to gather sufficient data to confirm the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…With respect to PML in patients without HIV, there are currently no approved therapies, although cytosine arabinoside, α-interferon, and cidofovir have been reported effective in some cases. Mefloquine, a widely used antimalarial agent, was recently reported to inhibit the JC virus infection in vitro (2) and produce some clinical improvement (3)(4)(5). Here, we report the beneficial effect of mefloquine in a case of PML associated with systemic lupus erythematosus (SLE).…”
Section: Introductionmentioning
confidence: 91%
“…With respect to PML in patients without HIV, there are currently no approved therapies, although cytosine arabinoside, α-interferon, and cidofovir have been reported effective in some cases. Mefloquine, a widely used antimalarial agent, was recently reported to inhibit the JC virus infection in vitro (2) and produce some clinical improvement (3)(4)(5). Here, we report the beneficial effect of mefloquine in a case of PML associated with systemic lupus erythematosus (SLE).…”
Section: Introductionmentioning
confidence: 91%
“…Mefloquine is known to cross the BBB and accumulate in the brain, where JCV infection is pathological (221,388), but has been associated with neurotoxicity (493). Several independent case reports showed that mefloquine treatment of PML was successful in reducing the viral burden in the brain and was associated with improvement of clinical symptoms (168,244). However, as reported at the 2011 annual meeting of the American Academy of Neurology, a multicenter clinical trial supported by Biogen-IDEC Inc. and Elan Pharmaceuticals failed to show a reproducible reduction in the JCV DNA in PML patient CSF or reduced clinical progression of PML in response to mefloquine treatment (150).…”
Section: Treatment Of Pml and Pml-irismentioning
confidence: 99%
“…Especially, neurologists are aware of the risk of PML when immunosuppressive therapy including natalizmab is used to treat multiple sclerosis [4]. Cases in which mefloquine therapy was effective have been reported [5,6].…”
Section: Discussionmentioning
confidence: 99%